Description of the labour market status of young people in selected countries of the European Union – the taxonomic approach - Trzpiot, Grażyna (Ocena sytuacji na rynku pracy osób młodych w wybranych krajach Unii Europejskiej – podejście taksonomiczne, 2021)
The primary objective of the article was to classify objects that are labour markets of young people in selected EU countries in order to create relatively homogeneous groups based on the set of variables considered. This allowed to examine the similarities of the selected member states and to compare the two years of 2008 and 2018. The analysis used EUROSTAT (17 macroeconomic and demographic variables) data for selected EU countries. The study used hierarchical methods to agglomerate objects through a dendrogram to illustrate the linkages between countries applying Ward's method for Euclidean distances. A non-hierarchical k-means method was also used to examine the allocation of objects and assess the relevance of the study by minimizing the variability within the resulting clusters, thereby maximizing the variability between them. The results provide a basis for improving the measurement of the situation of young people in the labour market by showing factors significantly influencing the level of employment and unemployment of young people. This study opens the door to future research on the labour market situation in the member states.
Econometrics = Ekonometria, 2021, Vol. 25, No. 4, s. 17-39
Keywords: labour market; cluster analysis; taxonomic approach; European Union countries; rynek pracy; analiza skupień; podejście taksonomiczne; kraje Unii Europejskiej